Recent Advances In Nanoparticles For Anti-Diabetic Therapy (Journal of Pharmaceutical Negative Results, 2022)
The use of nanoparticles in diabetes research has facilitated the creation of new insulin delivery systems that have the potential to significantly enhance diabetics' quality of life. The development of nanoparticle drug delivery systems for the treatment of diabetes has made it possible to deliver small molecule medications more effectively, which could significantly enhance the quality of life for diabetics. The use of nanoparticles in drug delivery to target the tissue for the treatment of diseases like diabetes is one of the major uses of nanoparticles in the field of medical science. To enable the administration of insulin through the best pathways possible without the need for injection, such as via oral or nasal routes, nanoparticles have been proposed as insulin carriers. Nanoparticles are defined as particles in the nanometer range that can be made from a variety of substances (such as polysaccharides, synthetic polymers, and lipids) and are frequently used to increase the loaded drug's bioavailability and physicochemical stability. This review discusses the use of various nanoparticle types, such as metallic, synthetic, polymeric, and lipid nanoparticles, to enhance the loaded drug's physicochemical stability and increase its bioavailability in comparison to conventional treatments. In this review article, we highlight recent developments in nanoparticle therapy and their therapeutic applications in the treatment of diabetes. This review's objective is to shed more light on recent developments and the influence of nanoparticles on biomedical sciences in the fight against diabetes.